Study of Release of Biologically Active Compounds from Cord Blood Under Different Conditions of Low-Temperature Impact - Moisieieva, Nataliia; Shcheniavskyi, Ivan; Gorina, Olga; Akhatova, Yuliia; Semenchenko, Oleksandr (Problems of Cryobiology and Cryomedicine, 2023)
Here, we have studied the impact of cord blood destruction method on composition of the cord blood-derived low molecular fractions, and compared the cryodestruction with other methods of cell destruction before extracting. Human cord blood was destroyed by rapid or slow freezing / warming, hypotonic lysis and thermal destruction. The obtained substance was used to produce the cord blood fraction (CBF) by multi-stage ultrafiltration and lyophilization. Dry weight, CBF composition and total protein content in them were evaluated by chromatographic profiles (gel permeation and reverse-phase high-performance liquid chromatography). The CBFs, obtained by different techniques for cord blood destruction were established to differ in the content and molecular weights of the components. These findings suggest the possibility to vary the amount and range of low molecular weight compounds in lyophilized cord blood fractions by using low temperatures and combining different regimens of freezing / warming. Probl Cryobiol Cryomed 2023; 33(4): 250–262